2011
DOI: 10.1002/jbio.201100067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between TEWL and laser scanning microscopy measurements for the in vivo characterization of the human epidermal barrier

Abstract: The analysis of the skin barrier properties is important in various fields of medical treatment and cosmetology. The development and improvement of topically applied substances require an objective analysis of the skin barrier characteristics. Transepidermal water loss (TEWL) measurement is the standard method to characterize epidermal barrier function. The most important disadvantage of this method though, is that it can be affected by different exogenous and endogenous factors, e.g. water content of the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Thus, measuring the reflectance of light in the SWIR range was proposed for interrogation of moisture and microscopic structural changes . We further surmise that the SWIR light reflectance sensitivity to tissue factors and moisture could also make it an important marker of skin tissue viability in burns, as suggested by the correlation between water loss and epidermal barrier dysfunction . Previous literature, especially in dermatologic journals, has characterized the composition of healthy cutaneous tissues.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Thus, measuring the reflectance of light in the SWIR range was proposed for interrogation of moisture and microscopic structural changes . We further surmise that the SWIR light reflectance sensitivity to tissue factors and moisture could also make it an important marker of skin tissue viability in burns, as suggested by the correlation between water loss and epidermal barrier dysfunction . Previous literature, especially in dermatologic journals, has characterized the composition of healthy cutaneous tissues.…”
Section: Introductionmentioning
confidence: 73%
“…Namely, strong water signals have been characterized within the stratum corneum and viable epidermis . Furthermore, studies investigating compositional changes after mechanical damage to the cutaneous layer have demonstrated increases in transepidermal water loss, that is, decrease in moisture content . Thus, in Figure , we illustrate the derived postulate that in viable skin that is well hydrated, increased water content preferentially attenuates the reflectance of the 1,940 nm wavelength compared to the 1,650 or 1,200 nm.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Vergou et al reported the comparison between transepidermal water loss and LCM measurements. 4 Most experiments were performed in air because it is natural. Conversely, this study focused on the dynamics of the SC in an aqueous solution.…”
mentioning
confidence: 99%